Novel ZnMgO ferroelectric material and preparation method thereof

By using low-temperature plasma enhanced molecular beam epitaxial method on metal substrates, and optimizing the process, the problem of ferroelectric performance optimization of ZnMgO materials in the prior art is solved, and high-quality and high-performance ferroelectric materials are achieved Preparation has promoted the application of ferroelectric materials.

CN119451542APending Publication Date: 2025-02-14CHANGCHUN INST OF OPTICS FINE MECHANICS & PHYSICS CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411639698.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the ferroelectric performance research of magnesium-doped zinc oxide (ZnMgO) materials mainly focuses on the optimization and understanding of structural and electrical characteristics, and lacks high-quality and high-performance preparation methods and process optimization.

Method used

The low-temperature plasma enhanced molecular beam epitaxial method (MBE) is used to grow ZnMgO ferroelectric films on metal substrates, and the crystal quality and ferroelectrodeization of ZnMgO are improved by optimizing growth process, annealing process and electrode superposition.

Benefits of technology

It has achieved the preparation of high-quality and high-performance ZnMgO ferroelectric materials, with excellent ferroelectric properties, can be compatible with traditional semiconductor processes, and promote the application of ferroelectric materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451542A_ABST
    Figure CN119451542A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ferroelectric materials, in particular to a novel ZnMgO ferroelectric material and a preparation method thereof. The novel ZnMgO ferroelectric material comprises a substrate, a bottom conductive layer, a ZnMgO ferroelectric film layer and a top electrode which are tightly stacked from bottom to top in sequence, the crystal structure of ZnMgO is a single wurtzite crystal structure, and the content of Mg is 10-55%. The thickness of the bottom conducting layer is 50-200 nm, the thickness of the ZnMgO ferroelectric film layer is 100-800 nm, and the thickness of the top electrode is 50-300 nm. The method has the advantages that the ZnMgO ferroelectric material is grown on the metal substrate through molecular beam epitaxy (MBE) low-temperature epitaxy, the single wurtzite high-magnesium component and excellent ferroelectric performance are achieved, the method can be well compatible with a traditional semiconductor technology, and application of the ferroelectric material is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferroelectric materials, and in particular to a novel ZnMgO ferroelectric material and a preparation method thereof. Background Art

[0002] Ferroelectric materials refer to dielectric materials with spontaneous polarization properties. Under the action of an external electric field, the electric dipole moment inside this material can change direction, and when the external electric field is removed, these electric dipole moments can still maintain their original direction, thus showing residual polarization characteristics. This spontaneous polarization of ferroelectric materials can be reversed by an external electric field within a certain temperature range (below the Curie temperature), so they have nonlinear and hysteresis characteristics.

[0003] Ferroelectric materials can be traced back to 1665, when a French pharmacist prepared Roche salt for the first time in Roche. In 1920, Joseph Valasek observed spontaneous polarization and hysteresis loop curves when studying potassium titanate (KNaSO4), marking the first discovery of ferroelectric materials. In 1935, P. Debye and F. Jona conducted in-depth research on the physical mechanism of ferroelectricity and proposed the molecular mechanism theory of ferroelectric materials, which laid a theoretical foundation for subsequent material research. 1938: German scientist Ernst Ising proposed the famous Ising model to explain the phase transition phenomenon in magnetism and ferroelectricity. In 1944, barium titanate (BaTiO3) was synthesized for the first time and quickly became one of the most important ferroelectric materials, widely used in capacitors and piezoelectric devices. In 1949, MJ Buerger proposed a crystal structure model of barium titanate to explain its ferroelectricity and electro-optical effect. Early 1950s: Lead zirconate titanate (PZT) material was developed, which combined the advantages of barium titanate and lead zirconate and became a widely used ferroelectric and piezoelectric material. In 1951, British scientists E. Fatuzzo and W. Merz conducted in-depth research on the domain structure and switching mechanism of ferroelectric materials, providing theoretical guidance for practical applications. In the 1960s, the application of ferroelectric materials in electronics and optoelectronics began to become popular, especially in capacitors and ferroelectric memories. In 1970, researchers developed ferroelectric ceramic materials such as barium strontium titanate (BST), which played an important role in microwave electronics. In the 1980s, the concept and research of ferroelectric memory (FeRAM) marked an important breakthrough in ferroelectric materials in the field of microelectronics. Early 1990s: Advances in ferroelectric thin film technology made it possible to use ferroelectric materials in integrated circuits. In 1993, the first non-volatile memory sample based on ferroelectric materials was launched. In 1995, JF Scott and CA Paz de Araujo developed a new material system for ferroelectric memory, making FeRAM technology more mature. In the early 2000s, nano-ferroelectric materials and multifunctional composite materials became research hotspots, promoting the application of ferroelectric materials in microelectromechanical systems (MEMS) and sensors. In 2003, ferroelectric thin films at the nanoscale were prepared for the first time, and size effects were observed, which is of great significance to the development of microelectronic devices. In 2007, progress was made in the spintronics research of ferroelectric materials, further expanding the application field of ferroelectric materials. In 2010, a new generation of wurtzite ferroelectric materials was developed. In 2013, a new type of thermoelectric device developed using ferroelectric materials came out, demonstrating the application prospects of ferroelectric materials in the energy field. In 2020 and beyond, ferroelectric materials continue to develop in the direction of high performance, multifunctionality and sustainability, especially in the fields of quantum computing, ultra-high-speed memory and new sensors, and researchers continue to explore new ferroelectric material systems and their application potential.

[0004] Ferroelectric materials have extensive and in-depth applications in many high-tech fields due to their unique spontaneous polarization characteristics and sensitivity to external electric fields. The application of ferroelectric materials specifically includes the following aspects: 1. Storage devices: Ferroelectric random access memory (FeRAM): FeRAM uses ferroelectric materials as the dielectric of capacitors. Its unique spontaneous polarization property allows information to be stored in the material through changes in polarization direction. Compared with traditional DRAM, FeRAM has faster write speeds, lower power consumption, and higher write life. In addition, FeRAM can maintain the non-volatility of data, and the data will not be lost even after power failure, which makes it widely used in embedded systems, smart cards and other fields.

[0005] 2. Sensors and actuators: (1) Piezoelectric sensors: Ferroelectric materials have a piezoelectric effect, which means that they generate charge or voltage when subjected to mechanical stress. Taking advantage of this property, ferroelectric materials are widely used in the manufacture of piezoelectric sensors, such as those used to detect pressure, acceleration, and sound waves. Such sensors are widely used in the automotive, medical, and industrial testing fields. (2) Ultrasonic transducers: Ferroelectric materials are also used to manufacture ultrasonic transducers, which can convert electrical energy into ultrasonic waves and receive echo signals. They are widely used in ultrasonic imaging and non-destructive testing.

[0006] 3. Energy harvesting: Piezoelectric energy harvester: Using the piezoelectric effect of ferroelectric materials, mechanical energy can be collected from vibrations, pressure changes or sound waves in the environment and converted into electrical energy. This energy harvesting technology has great potential in low-power devices (such as wireless sensor networks and wearable devices), enabling these devices to be autonomously powered and extend their service life.

[0007] 4. Display technology: Ferroelectric liquid crystal display (FLCD): Ferroelectric liquid crystal display is based on ferroelectric liquid crystal materials, and its response speed is much faster than traditional liquid crystal materials. This makes FLCD have high contrast, wide viewing angle and fast response time, and is suitable for high-resolution, fast dynamic display devices, such as flat-panel displays, head-mounted display devices, etc.

[0008] 5. Microelectronics and electrical devices: (1) Ferroelectric field effect transistor (FeFET): FeFET uses the polarization characteristics of ferroelectric materials as the gate dielectric of transistors, which gives transistors non-volatile storage capabilities. FeFET has important application prospects in logic circuits and memories, and can realize low-power, highly integrated storage and computing fusion chips. (2) Tunable filters: By applying different voltages, the dielectric constant of ferroelectric materials can be changed, which allows them to be used to make frequency-tunable filters, which are widely used in frequency selection in wireless communications.

[0009] 6. Electro-optical and optical equipment: (1) Electro-optic modulators: The electro-optic effect of ferroelectric materials can be used to manufacture electro-optic modulators. This device modulates optical signals by changing the refractive index of the material and has important applications in optical communications and laser technology. (2) Optical switches: Using the fast response time of ferroelectric materials, optical switches can achieve high-speed optical signal switching and are key components in optical communication networks.

[0010] 7. Infrared and thermal imaging: Infrared detectors: Certain ferroelectric materials are very sensitive to temperature changes and can be used to make infrared detectors. These detectors are widely used in night vision equipment, thermal imagers and remote sensing technology.

[0011] 8. Nonlinear optics: Frequency converters: The nonlinear optical properties of ferroelectric materials can be used in frequency converters, such as second harmonic generation (SHG) and parametric down conversion (OPG). These properties are of great significance in laser technology, optical communications and quantum optics.

[0012] 9. Capacitance and energy storage: Ferroelectric capacitors: Due to the high dielectric constant of ferroelectric materials, ferroelectric capacitors can achieve high energy density energy storage. Such capacitors can be used in high-power circuits, filters and RF modules.

[0013] Ferroelectric materials are driving innovation in multiple high-tech fields due to their diverse functional properties, especially in microelectronics, optoelectronics, sensors, and energy harvesting. In the future, with the advancement of materials science and nanotechnology, the application prospects of ferroelectric materials will be even broader.

[0014] At present, the research on the ferroelectric properties of magnesium-doped zinc oxide (ZnMgO) materials mainly focuses on the optimization and understanding of its structure and electrical properties. ZnMgO is a material whose physical properties are adjusted by doping Mg into ZnO. ZnO itself is a hexagonal wurtzite semiconductor with a band gap of 3.4 eV and has spontaneous polarization in the

[0001] direction. However, ZnO is not traditionally considered to be a ferroelectric material, but studies have shown that ZnMgO can exhibit reversible polarization through reasonable doping and stress adjustment. Through Mg doping, the crystal structure of ZnO can be significantly changed, thereby inducing ferroelectricity. The concentration of Mg doping is crucial to the lattice parameters, polarization behavior and phase stability of ZnMgO. When Mg doping reaches a certain level, ZnMgO films exhibit reversible spontaneous polarization, which is a key feature of ferroelectric materials. Especially at high Mg content, the polarization characteristics of ZnMgO still remain at a high level, which suggests that it has good material hardness and stability. This makes ZnMgO a potential new material in miniaturized and integrated ferroelectric devices.

[0015] The new generation of wurtzite ferroelectric material ZnMgO has great advantages over traditional ferroelectric materials, such as: standard hysteresis loop, large remnant polarization field, low coercive field, high Curie temperature, adjustable band gap 3.3~7.8eV, abundant raw materials, green and environmentally friendly, low growth temperature, etc. Summary of the invention

[0016] In order to solve the above problems, the present invention provides a novel ZnMgO ferroelectric material and a preparation method thereof.

[0017] The first object of the present invention is to provide a novel ZnMgO ferroelectric material, comprising: a substrate, a bottom conductive layer, a ZnMgO ferroelectric thin film layer and a top electrode which are closely stacked in sequence from bottom to top; The crystal structure of ZnMgO in the ZnMgO ferroelectric thin film layer is a single wurtzite crystal structure, and the Mg component is 10-55%.

[0018] Preferably, the bottom conductive layer has a thickness of 50-200 nm; the ZnMgO ferroelectric thin film layer has a thickness of 100-800 nm; and the top electrode has a thickness of 50-300 nm.

[0019] Preferably, the bottom conductive layer and the top electrode are prepared by magnetron sputtering, and the ZnMgO ferroelectric thin film layer is prepared by low-temperature plasma enhanced molecular beam epitaxy.

[0020] Preferably, the substrate is a c-plane sapphire substrate; the bottom conductive layer and the top electrode are both made of Pt.

[0021] The second object of the present invention is to provide a method for preparing a novel ZnMgO ferroelectric material, which specifically comprises the following steps: S1. Clean the substrate and blow dry; S2. placing the substrate into a vacuum chamber and depositing a bottom conductive layer on the substrate by magnetron sputtering; S3. A ZnMgO ferroelectric thin film layer is prepared on the surface of the bottom conductive layer by low temperature plasma enhanced molecular beam epitaxy; S4. Photolithography and development on the surface of the ZnMgO ferroelectric thin film layer to prepare a top electrode; S5. depositing metal on the surface of the ZnMgO ferroelectric thin film layer by magnetron sputtering, and performing stripping to obtain a top electrode; S6. The preparation of the new ZnMgO ferroelectric material is finally completed by overlay and wet etching processes on the prepared top electrode.

[0022] Preferably, step S3 specifically includes the following sub-steps: S301. Place the sample prepared in step S2 into the sample chamber, evacuate the sample, and move it into the growth chamber through the guide rail; S302. The substrate temperature is raised to 700-800°C for pretreatment for 1-2 hours. After the pretreatment, liquid nitrogen is introduced to reduce the substrate temperature to 350-450°C. Under the conditions of an oxygen source flow rate of 2-3 sccm, a radio frequency power of 200-400W, a zinc source temperature of 255-265°C, and a magnesium source temperature of 270-290°C, the substrate is turned on and rotated for 2-4 hours of growth. S303. After the growth is completed, turn off the RF, turn off the oxygen source, lower the temperature of the substrate, zinc source, and magnesium source to 75-85°C, turn off the substrate rotation, and take out the sample; S304. After annealing in an oxidizing atmosphere, the preparation of the ZnMgO ferroelectric thin film layer is completed.

[0023] Preferably, in step S302, the oxygen source flow rate is 2.2 sccm, the RF power is 210 W, the zinc source temperature is 260° C., and the magnesium source temperature is 280° C.

[0024] Preferably, the conditions for the annealing treatment in step S304 are: annealing pressure is normal pressure, annealing time is 0.5 to 2.5 hours, and annealing temperature is 500 to 950° C.

[0025] Preferably, step S5 specifically includes the following sub-steps: S501. Place the photolithographic sample into a magnetron sputtering vacuum chamber, fix the Pt target, evacuate to a certain value, introduce argon gas at a flow rate of 20-30 sccm, and after stabilization, perform metal Pt deposition at a radio frequency power of 150-400 W; S502. After the deposition is completed, the RF is turned off, the argon flow is turned off, the molecular pump is turned off, the speed is reduced to 0, the mechanical pump is turned off, the gas is inflated and the sample is taken out; after the sample is taken out, ultrasonic peeling is performed in acetone; S503. The sample is spin-coated with a positive photoresist using a coating machine, photolithography, development, washing in deionized water, and then dried with nitrogen; S504. The photolithographic sample is etched with hydrochloric acid to remove part of the ZnMgO ferroelectric thin film layer to expose the bottom conductive layer. The hydrochloric acid is etched for 1 to 3 seconds, and the sample is washed with deionized water and dried with nitrogen. The sample is ultrasonically peeled in acetone to complete the preparation.

[0026] Preferably, step S501 further includes: before metal deposition, pre-sputtering for 15 to 25 minutes is required to remove impurities on the surface of the target material.

[0027] Compared with the prior art, the present invention can achieve the following beneficial effects: The present invention uses MBE low-temperature epitaxy to provide a new path for preparing high-quality, high-performance ferroelectric material ZnMgO, and is well compatible with COMS. By optimizing the growth process, annealing process and electrode stacking method of ZnMgO, the crystal quality and ferroelectric polarization of ZnMgO are improved. The present invention uses molecular beam epitaxy (MBE) to grow ZnMgO ferroelectric material at low temperature on a metal substrate, and has a single wurtzite high-magnesium component ZnMgO, excellent ferroelectric properties, and is well compatible with traditional semiconductor processes, promoting the application of ferroelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart for preparing a novel ZnMgO ferroelectric material provided according to an embodiment of the present invention.

[0029] Figure 2 It is a schematic diagram of the structure of a novel ZnMgO ferroelectric material provided according to an embodiment of the present invention.

[0030] Figure 3 This is a microscopic magnified image of the novel ZnMgO ferroelectric material provided according to an embodiment of the present invention.

[0031] Figure 4 is a SEM image of a ZnMgO ferroelectric thin film layer provided according to an embodiment of the present invention.

[0032] Figure 5 1 is an XRD diagram of a ZnMgO ferroelectric thin film layer provided according to an embodiment of the present invention.

[0033] Figure 6 This is a graph of test results of hysteresis loop characteristics of a novel ZnMgO ferroelectric material provided according to an embodiment of the present invention.

[0034] Figure 7 This is a graph of IV characteristic test results of a new ZnMgO ferroelectric material provided according to an embodiment of the present invention.

[0035] Reference numerals: 1. Substrate; 2. Bottom conductive layer; 3. ZnMgO ferroelectric thin film layer; 4. Top electrode. DETAILED DESCRIPTION

[0036] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the same modules are represented by the same reference numerals. In the case of the same reference numerals, their names and functions are also the same. Therefore, the detailed description thereof will not be repeated.

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.

[0038] The present invention provides a novel ZnMgO ferroelectric material, comprising: a substrate, a bottom conductive layer, a ZnMgO ferroelectric thin film layer and a top electrode which are stacked closely in sequence from bottom to top; The bottom conductive layer has a thickness of 50-200 nm, the ZnMgO ferroelectric thin film layer has a thickness of 100-800 nm, and the top electrode has a thickness of 50-300 nm; preferably, the top electrode has a thickness of 50-200 nm; The crystal structure of ZnMgO in the ZnMgO ferroelectric thin film layer is a single wurtzite crystal structure, and the Mg component is 10~55%; The substrate is a c-plane sapphire substrate; The bottom conductive layer and the top electrode are both made of Pt; The bottom conductive layer and the top electrode are prepared by magnetron sputtering, and the ZnMgO ferroelectric thin film layer is prepared by low-temperature plasma enhanced molecular beam epitaxy.

[0039] The preparation method of the above ZnMgO ferroelectric material specifically comprises the following steps: S1. Clean the substrate and blow dry; S2. placing the substrate into a vacuum chamber and depositing a bottom conductive layer on the substrate by magnetron sputtering; S3. A ZnMgO ferroelectric thin film layer is prepared on the surface of the bottom conductive layer by low temperature plasma enhanced molecular beam epitaxy; S4. Photolithography and development on the surface of the ZnMgO ferroelectric thin film layer to prepare a top electrode; S5. Deposit metal on the surface of the ZnMgO ferroelectric thin film layer by magnetron sputtering, and then peel off to obtain a top electrode.

[0040] S6. The preparation of the new ZnMgO ferroelectric material is finally completed by overlay and wet etching processes on the prepared top electrode.

[0041] Specifically, the epitaxial growth temperature in step S3 is 10-600°C.

[0042] Specifically, step S3 further includes: after the ZnMgO film is epitaxially grown, annealing is performed in an oxidizing atmosphere, and the annealing conditions are: annealing pressure is normal pressure, annealing time is 0.5-2.5 hours, and annealing temperature is 500-950°C.

[0043] Preferably, the oxidizing atmosphere is specifically oxygen.

[0044] Example 1 The present invention provides a novel ZnMgO ferroelectric material (such as Figure 1-Figure 3 As shown), comprising: a substrate 1, a bottom conductive layer 2, a ZnMgO ferroelectric thin film layer 3 and a top electrode 4 which are closely stacked from bottom to top; The substrate 1 is a substrate well known to those skilled in the art. In this embodiment, the substrate 1 is specifically c-plane sapphire; The surface of the substrate 1 is provided with a bottom conductive layer 2 (Pt conductive layer film), the thickness of which is about 100 nm; the thickness of the ZnMgO ferroelectric film layer 3 is about 300 nm.

[0045] The preparation method specifically comprises the following steps: S1. Clean the substrate and blow dry; Specifically, the c-plane sapphire was ultrasonically cleaned with acetone, ethanol, and deionized water for five minutes respectively, and dried with nitrogen in each step.

[0046] S2. Place the substrate in a vacuum chamber and deposit a bottom conductive layer on the substrate using a magnetron sputtering method; the specific operation is as follows: After cleaning, the c-plane sapphire is placed in the vacuum chamber, the Pt target is fixed, the growth temperature is set to room temperature, and the chamber is evacuated; after a certain vacuum degree is reached, Ar gas is introduced with a flow rate of 25sccm; after stabilization, the RF power is set to 150W and the deposition time is 30min; after the deposition is completed, the RF, Ar flow, and molecular pump are turned off, and the molecular pump is turned off after the speed drops below 100 rpm, and the sample is inflated and taken out; In order to improve the device quality, in step S2, pre-sputtering for 20 minutes is required to remove impurities on the Pt surface before deposition.

[0047] S3. A ZnMgO ferroelectric thin film layer is prepared on the surface of the bottom conductive layer by low temperature plasma enhanced molecular beam epitaxy; the specific operation is as follows: S301. Place the substrate on which the bottom conductive layer was deposited in step S2 into the injection chamber, first use a mechanical pump as a pre-pump for 10 minutes, then turn on the molecular pump for 2 hours, shake open the valve and place the tray on the trolley, place the tray into the growth chamber through the trolley, and close the valve; S302. The tray is heated to 750°C and pretreated for two hours; liquid nitrogen is passed through the pretreatment, the substrate temperature is 400°C during growth, the oxygen flow rate is 2.2sccm, the RF power is 210W, the zinc source is 260°C, the magnesium source is 280°C, and the growth is three hours; S303. After the growth is completed, the RF is turned off, the oxygen flow is turned off, the temperature of the substrate, the zinc source (referring to the pure substance of the chemical element Zn placed in the crucible), and the magnesium source (referring to the pure substance of the chemical element Zn placed in the crucible) is lowered to 80° C., and the sample is taken out; S304. Perform annealing in an oxygen atmosphere, the annealing conditions are: annealing pressure is normal pressure, annealing time is 2 hours, annealing temperature is 650° C.; complete the preparation of the ZnMgO ferroelectric thin film layer.

[0048] S4. Photolithography and development are performed on the surface of the ZnMgO ferroelectric thin film layer to prepare a pattern of the top electrode; the specific operation is as follows: S401. Spin-coat the negative photoresist on the sample prepared in step S3, and use the glue machine at 1000 rpm (pre-rotation) for 10s and 6000 rpm (actual rotation) for 20s; spin-coat the negative photoresist, bake on a 90°C hot plate for 8min, expose with a photolithography machine for 30s, and after the exposure is completed, bake on a hot plate at 90°C for 5 minutes to solidify the photoresist; S402. Develop in a developer for 6 seconds, rinse in deionized water for 2 minutes, blow dry with nitrogen, and complete photolithography to obtain a pattern of the top electrode.

[0049] S5. Depositing metal on the surface of the ZnMgO ferroelectric thin film layer by magnetron sputtering, peeling off, obtaining a top electrode, and completing the preparation of the new ZnMgO ferroelectric material; the specific operation is as follows: S501. Place the photolithographic sample into a magnetron sputtering vacuum chamber, fix the Pt target, and set the growth temperature to room temperature; evacuate the chamber to a certain vacuum degree, introduce Ar gas at a flow rate of 25 sccm, set the RF power to 150 W after stabilization, and set the deposition time to 30 min; during the top electrode deposition process, use a mask to deposit a top electrode array, and the specific size of the top electrode array is a 500-micron cylinder; Before deposition, pre-sputtering for 20 min is required to remove impurities on the Pt surface; S502. After the deposition is completed, turn off the radio frequency, turn off the Ar gas flow, and turn off the molecular pump after the rotation speed drops below 100 rpm, inflate, and take out the sample; after taking out the sample, ultrasonically peel it in acetone for 3 minutes; S503. By hydrochloric acid corrosion, part of the ZnMgO ferroelectric thin film layer is removed to expose the bottom conductive layer; S504. The sample was pre-spun at 1000 rpm for 10 s and then at 6000 rpm for 20 s using a coating machine, positive photoresist was spin-coated, baked on a 90°C hot plate for 6 min, exposed with a photolithography machine for 35 s, directly developed in a developer for 12 s, rinsed in deionized water for 2 min, and dried with nitrogen; S505. Take an appropriate amount of concentrated hydrochloric acid and prepare dilute hydrochloric acid in a volume ratio of 1:5, put the photolithographic sample into the dilute hydrochloric acid for corrosion for 2 seconds, wash it in deionized water for 1 minute, and blow it dry with nitrogen; then ultrasonically peel it in acetone for 3 minutes to complete the preparation of ZnMgO ferroelectric material.

[0050] The specific preparation process is shown in Figure 1The structural diagram and top view of the object are shown in Figure 2 and Figure 3 .

[0051] The ZnMgO ferroelectric material prepared in the example was subjected to structural and electrical tests.

[0052] The SEM test structure of the ZnMgO ferroelectric thin film layer made on the Pt bottom conductive layer is as follows Figure 4 As shown in the figure, it can be seen that the film is relatively flat, the thickness of the Pt bottom conductive layer is about 100nm, and the thickness of the ZnMgO film is about 300nm.

[0053] The XRD test structure of the ZnMgO ferroelectric thin film layer made on the Pt bottom conductive layer is as follows Figure 5 As shown in the figure, a diffraction peak near 35° can be observed, which corresponds to the (002) crystal diffraction of wurtzite ZnMgO, and a diffraction peak near 41°, which corresponds to the (111) crystal diffraction of Pt. XRD shows that the film quality is excellent.

[0054] The test results of the hysteresis loop characteristics of the device are as follows: Figure 6 As shown, it can be seen from the figure that the hysteresis loop of the material indicates that the device should be a ferroelectric material with large leakage.

[0055] The IV characteristics test results of the device are as follows: Figure 7 As shown in the figure, it can be seen that the device has a polarization reversal current and ZnMgO is a ferroelectric material.

[0056] The above tests prove that the ZnMgO material prepared by the present invention is a ferroelectric material, which can be used in memory, sensors, optoelectronic devices, etc. in the future, and has great significance for the application of ferroelectric thin films.

[0057] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the disclosure of the present invention can be performed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.

[0058] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A new type of ZnMgO ferroelectric material, characterized in that: include: A substrate, a bottom conductive layer, a ZnMgO ferroelectric thin film layer and a top electrode are closely stacked in sequence from bottom to top; The crystal structure of ZnMgO in the ZnMgO ferroelectric thin film layer is a single wurtzite crystal structure, and the Mg component is 10-55%.

2. A novel ZnMgO ferroelectric material according to claim 1, characterized in that: The bottom conductive layer has a thickness of 50-200 nm; the ZnMgO ferroelectric thin film layer has a thickness of 100-800 nm; and the top electrode has a thickness of 50-300 nm.

3. A novel ZnMgO ferroelectric material according to claim 1, characterized in that: The bottom conductive layer and the top electrode are prepared by magnetron sputtering, and the ZnMgO ferroelectric thin film layer is prepared by low-temperature plasma enhanced molecular beam epitaxy.

4. A novel ZnMgO ferroelectric material according to claim 3, characterized in that: The substrate is a c-plane sapphire substrate; the bottom conductive layer and the top electrode are both made of Pt.

5. A method for preparing a novel ZnMgO ferroelectric material according to any one of claims 1 to 4, characterized in that: The specific steps include: S1. Clean the substrate and blow dry; S2. placing the substrate into a vacuum chamber and depositing a bottom conductive layer on the substrate by magnetron sputtering; S3. A ZnMgO ferroelectric thin film layer is prepared on the surface of the bottom conductive layer by low temperature plasma enhanced molecular beam epitaxy; S4. Photolithography and development on the surface of the ZnMgO ferroelectric thin film layer to prepare a top electrode; S5. depositing metal on the surface of the ZnMgO ferroelectric thin film layer by magnetron sputtering, and performing stripping to obtain a top electrode; S6. The preparation of the new ZnMgO ferroelectric material is finally completed by overlay and wet etching processes on the prepared top electrode.

6. The method for preparing a novel ZnMgO ferroelectric material according to claim 5, characterized in that: The step S3 specifically includes the following sub-steps: S301. Place the sample prepared in step S2 into the sample chamber, evacuate the sample, and move it into the growth chamber through the guide rail; S302. The substrate temperature is raised to 700-800°C for pretreatment for 1-2 hours. After the pretreatment, liquid nitrogen is introduced to reduce the substrate temperature to 350-450°C. Under the conditions of an oxygen source flow rate of 2-3 sccm, a radio frequency power of 200-400W, a zinc source temperature of 255-265°C, and a magnesium source temperature of 270-290°C, the substrate is turned on and rotated for 2-4 hours of growth. S303. After the growth is completed, turn off the RF, turn off the oxygen source, lower the temperature of the substrate, zinc source, and magnesium source to 75-85°C, turn off the substrate rotation, and take out the sample; S304. After annealing in an oxidizing atmosphere, the preparation of the ZnMgO ferroelectric thin film layer is completed.

7. The method for preparing a novel ZnMgO ferroelectric material according to claim 6, characterized in that: In step S302, the oxygen source flow rate is 2.2 sccm, the RF power is 210 W, the zinc source temperature is 260° C., and the magnesium source temperature is 280° C.

8. The method for preparing a novel ZnMgO ferroelectric material according to claim 6, characterized in that: The conditions of the annealing treatment in step S304 are: annealing pressure is normal pressure, annealing time is 0.5 to 2.5 hours, and annealing temperature is 500 to 950° C.

9. The method for preparing a novel ZnMgO ferroelectric material according to claim 5, characterized in that: The step S5 specifically includes the following sub-steps: S501. Place the photolithographic sample into a magnetron sputtering vacuum chamber, fix the Pt target, evacuate to a certain value, introduce argon gas at a flow rate of 20-30 sccm, and after stabilization, perform metal Pt deposition at a radio frequency power of 150-400 W; S502. After the deposition is completed, the RF is turned off, the argon flow is turned off, the molecular pump is turned off, the speed is reduced to 0, the mechanical pump is turned off, the gas is inflated and the sample is taken out; after the sample is taken out, ultrasonic peeling is performed in acetone; S503. The sample is spin-coated with a positive photoresist using a coating machine, photolithography, development, washing in deionized water, and then dried with nitrogen; S504. The photolithographic sample is etched with hydrochloric acid to remove part of the ZnMgO ferroelectric thin film layer to expose the bottom conductive layer. The hydrochloric acid is etched for 1 to 3 seconds, and the sample is washed with deionized water and dried with nitrogen. The sample is ultrasonically peeled in acetone to complete the preparation.

10. The method for preparing a novel ZnMgO ferroelectric material according to claim 9, characterized in that: The step S501 also includes: before metal deposition, pre-sputtering for 15 to 25 minutes is required to remove impurities on the surface of the target material.